Factors Influencing Continuance Intention to Play Online Games - Boniface Boliona Badilangoe Keraf; Edwin Pramana; Gunawan (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
This study aims to identify and analyze the factors influencing continuance intention in playing online games, a rapidly growing global entertainment sector that attracts players from diverse backgrounds. Using the Expectation Confirmation Model (ECM), this research explores the psychological and behavioral aspects that drive players to continue playing. To achieve this objective, data were collected through a survey using Google Forms distributed to schools, colleges, and social media. A total of 505 active player responses were collected, and 469 valid data entries were retained after screening. The analysis was conducted using Structural Equation Modeling (SEM) with SPSS and AMOS software to identify the impact of each factor. The results from SPSS and AMOS calculations showed that Flow was not significant, and Engagement was excluded due to failing the validity test. These findings help developers and policymakers better understand player motivations to create more effective strategies for building a sustainable gaming industry. The study found that Social Influence had the greatest impact on continuance intention. Players were more likely to continue playing if the game was popular in their environment or had a large market. This factor fosters a sense of community and social support among players, from friends, family, and communities who play the same game. Perceived Usefulness and Perceived Enjoyment followed, contributing significantly as well.